Nuclear power in China: Its role in national energy policy - Philip Andrews-Speed (The Oxford Institute for Energy Studies, 2023)
With an installed capacity of 56 GWe, China has the world's third largest fleet of civil nuclear reactors after the U.S. and France and its ambitious expansion programme will give it the largest fleet by 2030. The government's policy objectives driving this programme are fourfold: enhancing security of energy supply, reducing carbon dioxide emissions, promoting advanced industrial and technological development, and boosting technology exports. In 2021, nuclear power provided roughly 4.8 per cent of China's electricity supply, 2.3 per cent of primary commercial energy supply and 25 per cent of non-hydro, low-carbon electricity. The country has made great progress in catching up with the most advanced developments in other countries, notably with Generation III and high-temperature gas-cooled reactors. However, it still struggles to deliver more sophisticated technologies such as fast reactors, advanced fuel development and reprocessing. Despite claims that up to 30 nuclear reactors would be built across the world by 2030 as part of the Belt and Road Initiative, the only new overseas plants to have been built recently are in Pakistan. Meanwhile, construction of new reactors within China continues apace and installed capacity could exceed 300 GWe by 2050. At the same time, new technologies are being developed that could allow Chinese companies to become the world's dominant vendors of nuclear reactors in the future.
Keywords: 330; carbon emissions; China; energy security; Nuclear Power; Technology